Non-genomic effects of steroid hormones: role of ion channels - Straltsova, Darya Y.; Charnysh, Maryia A.; Hryvusevich, Palina V.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2019)
In animals, steroid hormones can act using genomic and non-genomic mechanisms. Plant steroid hormones, brassinosteroids, are capable of inducing the expression of some gene ensembles, however their non-genomic pathways for triggering the physiological effects are still unclear. In this paper, we propose the hypothesis on existence of brassinosteroid non-genomic effects in plant cells. This non-genomic pathway could due to modulation of ion channel activities and modification of membrane receptors.
Keywords: steroid hormones; brassinosteroids; non-genomic effects of hormones; genomic action of hormones; ion channels